Abiraterone Acetate and Castration Resistant Ductal Adenocarcinoma of the Prostate - Edgar Linden-Castro; Marcela Pelayo-Nieto; Alejandro Alias-Melgar; Daniel Espinosa-Perezgrovas; Ivan Ramirez-Galindo; Gabriel Catalan-Quinto (Case Reports in Urology)
Ductal adenocarcinoma of the prostate is a rare histological variant that only represents <1% of prostate tumors. This histological variant has several important clinical implications with respect to their evolution, clinical prognosis, and treatment. We report the case of a 64-year-old patient with ductal adenocarcinoma of the prostate, which progresses to castration-resistant prostate cancer, that was treated with abiraterone acetate with good clinical response, to our knowledge, the first case of ductal adenocarcinoma of the prostate in treatment with abiraterone acetate.